Air cloud algorithm for diminution of active power loss - Lenin, Kanagasabai (Institute of Advanced Engineering and Science, 2020)
In this work, air cloud (AC) algorithm is used to solve the optimal reactive power problem. Clouds shape in numerous ways. Convective clouds are created when moist air is warmed and expand into floating. Air raises haulage water vapour and within it expands and gets cooled as it goes. As the temperature and pressure of the air diminish, its saturation point – the equilibrium level of evaporation and condensation – is reduced. Every x is one cloud droplet, and qualitative characteristic of one cloud is explained by the three digital character (Ex, En, He), droplets number n, where Ex (Expected value), En (Entropy) and He (Hyper entropy) of one cloud determine centre position of cloud, cover range of cloud and thickness of cloud equally. Projected AC algorithm has been tested in standard IEEE 14, 57, 300 bus systems and simulations results show the better performance of the proposed algorithm in reducing the real power loss.